Effect of bisphosphonates on the crystallization of stone-forming salts in synthetic urine - Kovacevic, Larisa (Investig Clin Urol, 2020)
PURPOSE: We investigated the inhibitory effect of bisphosphonates (BPs) on the crystallization of calcium oxalate monohydrate (COM), calcium phosphate (CaP), and magnesium ammonium phosphate (MAP) in synthetic urine, aiming to see 1) which specific BPs work best on a particular type of crystal and 2) what is the lowest concentration of BPs that inhibits crystal formation. MATERIALS AND METHODS: Crystals from synthetic urine were exposed to different concentrations of BPs. Urinary turbidity was used as a marker of crystallization and was measured by spectrophotometry by use of a validated method in our laboratory. The percent inhibitory activity (IA) was calculated by using the formula: (a−b )/a×100, where a is baseline maximal turbidity and b is maximal turbidity with various concentrations of medication. Potassium citrate and magnesium citrate were used as positive controls. RESULTS: At the lowest dose of 0.001 mg/mL, risedronate induced the highest IA of 37% on CaP, whereas ibandronate had the strongest IA on COM (24%). To initiate the inhibition of MAP crystallization, risedronate required a two-fold higher concentration (0.002 mg/mL) to reach 30% IA, whereas etidronate required a four-fold higher concentration (0.004 mg/mL) to reach 42% IA. CONCLUSIONS: BPs are good inhibitors of crystallization in synthetic urine, with risedronate and ibandronate being the most potent. At a low clinically acceptable dose, their highest inhibitory action was on CaP and COM crystals. Higher doses were needed to prevent MAP crystallization. Further investigation of the use of BPs in kidney stone prevention is warranted.